Factors and conditions that influence noncompliance to medical regimen among diabetic patients treated in federal medical centre Owerri - Chikodi, Ezeama Matina; Olivia, Iwu A.; Enwereji, Ezinna Ezinne (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes mellitus poses a major global health threat worldwide. Compliance to prescribed regimen helps to reduce complications and death, but the rate of compliance has been consistently low in developing countries. This study therefore identified factors and conditions that influence compliance to medical regimen among diabetic patients treated in federal medical centre Owerri. Methods: Descriptive survey design was adopted. A convenience sampling technique was used to recruit all the 68 diabetic patients receiving treatment in the out-patients’ male and female wards. Data were collected using administered questionnaire. Data were analyzed and presented with percentages, tables and graphs. Results: The result showed low level of compliance among 37 (54.4%) of the diabetic patients treated in federal medical center Owerri. Factors that influenced compliance as indicated by the respondents include; drugs that are taken for a long time 23 (33.8%), long waiting time before seeing a doctor as well as the distance covered to the facility and diet restriction 22 (32.3%) respectively. Other factors that contributed to poor compliance included: inability to afford monitoring machine 16 (23.5%), and unaffordability of diabetic drugs 15 (23.5%). Majority (73.5%) of the patients suggested good communication as the best measure to promote patient’s compliance. Conclusions: This study identified that several factors contributed to lack of diabetic patients’ compliance to medical regimen and that only good communication can encourage patients’ compliance. Therefore, good communication between the health care givers and diabetic patients should be encouraged.